Myocardial infarction and oxidative damage in animal models: objective and expectations from the application of cysteine derivatives. (2nd January 2023) - Angelovski, Marija; Hadzi-Petrushev, Nikola; Mitrokhin, Vadim; Kamkin, Andre; Mladenov, Mitko
Abstract: Reactive oxygen species (ROS) and associated oxidative stress are the main contributors to pathophysiological changes following myocardial infarction (MI), which is the principal cause of death from cardiovascular disease. The glutathione (GSH)/glutathione peroxidase (GPx) system appears to be the main and most active cardiac antioxidant mechanism. Hence, enhancement of the myocardial GSH system might have protective effects in the setting of MI. It follows that by increasing antioxidant capacity, the heart will be able to reduce the damage associated with MI and even prevent/weaken the occurrence of oxidative stress, which is highly ranked among the factors responsible for the occurrence of acute MI. For these reasons, the primary goal of future investigations should be to address the effects of different antioxidative compounds and especially cysteine derivatives like N -acetyl cysteine (NAC) and L -2-oxothiazolidine-4-carboxylic acid (OTC) as precursors responsible for the enhancement of the GSH-related antioxidant system's capacity. It is assumed that this will lay down the basis for elucidation of the mechanisms throughout which applicable doses of OTC will manifest a potentially positive impact in the reduction of adverse effects of acute MI. The inclusion of OTC in the models for prediction of the distribution of oxygen in infarcted animal hearts can help to upgrade existing computational models. Such a model would be based on computational geometries of the heart, but the inclusion of biochemical redox features in addition to angiogenic therapy, despite improvement of the post-infarcted oxygenated outcome could enhance the accuracy of the predictive values of oxygenation.